Foetus acardius amorphous - report of two cases - Gjorgjievska, Aneta; Ristovski, Gligor; Zdravkovski, Panche; Kostadinova Kunovska, Slavica; Spasevska, Liljana; Petrushevska, Gordana (Macedonian Association of Pathology, 2016)
Objective: Foetus acardius amorphous is a rare congenital malformation with an incidence of 1:35000 births, which usually is a complication in multiple pregnancies. The main diagnostic dilemma is placental teratoma, a non-trophoblastic, extremely rare tumor, with only 27 cases reported in the literature. We present a case of a triplet pregnancy of a 35-year-old mother and a twin pregnancy of a 32-year old mother. Material and Methods: Case 1. Along with three live births, there was a teratogenic, skin-covered, oval tumor mass, weighing 1450 grams and 21x15x6 cm in size, with two epidermal buds with a diameter of 2-3 cm on the surface. On dissection, there were fatty tissue, muscle, cartilage, bone and large intestinal loops. Case 2. Along with a stillbirth, there was an oval, skin-covered structure weighing 67 grams and diameter of 9.5 cm, with visible elongated bud, resembling a limb, at one pole. The dissection showed autolytic organoid structures and cavities. Results: There are a few criteria for differentiating acardiac fetus from placental teratoma: a presence of umbilical cord, skeletal structures, visible rudimentary extremities and partially developed visceral organs. On the other hand, a placental teratoma is predominantly composed of a disorganized collection of mature tissues. The gross and histological findings solved our diagnostic dilemma. Conclusions: There is a great overlap between these two entities and the proposed criteria are useful only in clear cases. Some authors consider them as different levels of development and differentiation of a single pathological event. Nonetheless, the clinical information for multiple gestation pregnancies is very important and helpful for diagnosing foetus acardiacus.
Keywords: foetus; malformation; teratoma